School-Based Digital Innovation Challenges and Way Forward Conversations about Digital Transformation in Education - James Sunney Quaicoe; Abiodun Afolayan Ogunyemi; Merja Lina Bauters (MDPI AG, 2023)
Background: This article attempts to formulate a school-based model to capitalise on the opportunities and strengths within schools in the Sub-Saharan Africa (SSA) regions to ideate global school-driven digital innovation(s). Consequently, this article explores various digital innovation challenges, opportunities, and elements for schools, as well as proposed school-driven interventions. The paper seeks to open conversations among various international bodies and educational stakeholders, leading to school actors taking ownership of educational projects and school innovation. Methods: A traditional literature review was adopted to analyse the subject of Digital Transformation in Education (DTE). The traditional literature review is a comprehensive and critical overview based on the past and current literature on a subject matter without stringent methodology. Through the literature review methodology, existing materials on the subject matter are subsequently used. Terms and concepts about school innovation and management/leadership were extracted for consideration. These served as a basis for formulating a reference DTE model for interventions. This paper is underpinned by two main conceptual and theoretical bases: (i) The theory of school-based management and its related indicators, and (ii) Michael Fullan's concept of school innovation, which is based on the three key factors of Technology, Pedagogy, and Change knowledge. Fullan's concept is extended to showcase how Active Learning (AL) can inform pedagogical innovation. Results: This paper presents a school-based digital transformation in the education reference model as the outcome. The model uses concept maps to showcase the interrelations between DTE indicators and concepts, and the linkages around which Digital Transformation in Education could be developed as a School-Based Managed (SBM) agenda.